Comparison of reliability of 100 nm AlGaN/GaN HEMTs with T-gate and SAG-gate technology. (September 2018) - Dammann, M.; Baeumler, M.; Brückner, P.; Kemmer, T.; Konstanzer, H.; Graff, A.; Simon-Najasek, M.; Quay, R.
Abstract: The effect of gate technology and semiconductor passivation on the switching speed and device reliability has been investigated. By reducing the parasitic capacitances and reducing the passivation induced surface charge density a median lifetime of around 10 6 h at a channel temperature of 125 °C and a current-gain cut-off frequency of 74 GHz for a T-gate technology has been achieved. By electroluminescence and TEM cross-sectioning of a stressed device a local inhomogeneous pit formation process was found as the major degradation mechanism for the decrease of the saturation current.